2019
DOI: 10.1186/s12933-019-0870-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines in type 2 diabetes mellitus as facilitators of hypercoagulation and abnormal clot formation

Abstract: Background: The global burden of type 2 diabetes mellitus (T2DM), together with the presence of cardiovascular risk in this population, is reaching pandemic levels. A prominent feature of T2DM is chronic and systemic inflammation, with the accompanying presence of circulating and dysregulated inflammatory biomarkers; which in turn is associated with abnormal clot formation. Methods:Here, we investigate the correlation between abnormal blood clotting, using thromboelastography (TEG), clot ultrastructure using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 83 publications
7
97
0
Order By: Relevance
“…Fibrinogen is a large, extracellular protein, synthesised by the liver and mainly found in the blood [33][34][35]. Fibrinogen is also an acute-phase protein that is upregulated during inflammation [33,36,37]. Upregulation of fibrin(ogen) is associated with hypercoagulability and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen is a large, extracellular protein, synthesised by the liver and mainly found in the blood [33][34][35]. Fibrinogen is also an acute-phase protein that is upregulated during inflammation [33,36,37]. Upregulation of fibrin(ogen) is associated with hypercoagulability and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen is a large, extracellular protein, synthesised by the liver and mainly found in the blood [31][32][33].) Fibrinogen (normal levels between 2 -4 mg/mL) is also an acute-phase protein that is upregulated during inflammation [31,34,35]. Upregulation of fibrin(ogen) is associated with hypercoagulability and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, women have been reported to have a decrease in ammatory response in comparison to men due to a rapid decline in sex-steroid during reproductive senescence [24]. Previously, researchers often combine men and women into control and experimental groups [26][27][28]. When we combine men and women in the control and experimental, there is no difference between participants with normal and high HbA1c (Fig.…”
Section: Discussionmentioning
confidence: 93%